The Existence of Consumer Protection in the Perspective of Cyber Law in Indonesia - Fajar Ari Sudewo; Dinar Mahardika (Faculty of Law, Universitas Jenderal Soedirman, 2022)
The subject matter of this research is about how consumer protection is regulated in cyber law in Indonesia. Legal protection of consumers in buying and selling transactions through electronic media is regulated in Law Number 8 of 1999 concerning Consumer Protection, Law Number 7 of 2014 concerning Trade and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. The type of research used in this research is library research with a normative basis. While the approach used by the author is the statute approach so that the primary source of material is obtained from statutory literature, minutes or official records in making legislation, and judges' decisions. The research results show: First, the need to create a consumer protection system that contains elements of legal certainty. Second, legal protection for consumers in buying and selling transactions through electronic media consists of two concepts of legal protection, namely preventive legal protection and repressive legal protection.Keywords: Legal Protection, Consumers; Electronic buying and selling transactions